THE KNOWLEDGE OF AGRICULTURE EXTENSION MANAGERS ON THE STRATEGIC MANAGEMENT IN THE PROVINCES OF THE MIDDLE REGION OF IRAQ. - & Naji, Al-Dulaimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The objective of this research to determine the knowledge level of the agriculture extension managers in the strategic management, To achieve the aims of this study we used a questionnaire included with a quadrant scale and consists of 75 paragraph for the managers of the middle zone and the executive directors, distributed in 12 sectors ( Concept, the importance, aims, types of strategies, level of strategies, Vision Characteristics, Mission Characteristics , strategic analysis, strategy formulation, strategy application, adjustment of the strategy, role and duties of the strategic manger). A random samples of 50 managers and vice managers have been taken from the middle zone of Iraq (Baghdad, Babylon, Najaf, Karbalaa, Wasit, Dyala). Moreover, another random samples represents 40% of each of the directors and executive management categories of 80 employees to be a total sample size 130 Director. The results of the study showed the average level of knowledge was 143,46 degree for the managers of the middle zone, and 135,88 degree for the executive directors on a knowledge scale ranges from to 225 degree and consists of 75 paragraph. 48% of the managers of the middle zone and 55% of the executive directors has a medium level of knowledge, accordingly this study recommend the importance of qualifying the agriculture extension managers and to develop their capabilities and skills in the field of the strategic management through specialized training programs. Moreover, the Ministry of Agriculture should take in account the importance of the strategic management and its role in achieving the agriculture development and should work to enhance its application.